Cretien van Campen. The Proust Effect – The senses as doorways to lost memories - Westerhof, Gerben; Stevens, Carlijn (Tijdschrift voor Gerontologie en Geriatrie, 2015)
Bespreking:Cretien van Campen. The Proust Effect – Thesenses as doorways to lost memories. OxfordUniversity Press. ISBN 9870199685875.